Surgery for diverticular peritonitis - Papagrigoriadis, Savvas; Charalampopoulos, Anestis (Frontiers in Medicine, 2025)
Some patients with acute diverticulitis will present with colonic perforation and peritonitis. This paper is a review of the surgical management of diverticular peritonitis Hinchey III and Hinchey IV. The significance of prompt management of sepsis is discussed. The surgical options for Hinchey III and Hinchey IV peritonitis are discussed with presentation of the supporting literature. In Hinchey III peritonitis Laparoscopic Peritoneal Lavage has emerged as an alternative to laparotomy—colectomy. The classic Hartmann’s operation has no advantage of survival and results frequently in permanent stoma. Recent published evidence supports on table colonic lavage and the performance of primary anastomosis unless the patient is critically ill.